Reception of climate activist messages by low-carbon transition actors: argument evasion in the carbon offsetting debate. (4th May 2022) - Üzelgün, Mehmet Ali; Fernandes-Jesus, Maria; Küçükural, Önder
Abstract: How do adherents to hegemonic discourses construe and respond to radical arguments by activists? To address the question, we examined how adherents to hegemonic climate change discourses react to a climate activist's arguments. In interviews conducted with corporate actors of low-carbon transitions, we used a video excerpt to elicit critical reactions to an activist's argumentation on carbon offsetting. We used the critical reactions as an index of interviewees' reception of the activist's case and pragma-dialectical theory to analyze them. We found that interviewees advanced four types of criticism concerning individual agency, awareness-raising, neutralization, and financial instruments. We discuss their inter-relations and how interviewees construed the activist's argumentation in ways that evaded his more antagonistic claims.